The Neolithic Refitting from Gebel Ramlah, the Western Desert of Egypt. (1st October 2016) - Mugaj, Jakub
Abstract : This paper presents results of the refitting analysis of one-nodule processing from the Neolithic site in Gebel Ramlah, the Western Desert of Egypt. The analysis consists of technological and spatial aspects. Examination of the refitting and previous research conducted by the Combined Prehistoric Expedition near the Nabta-Kiseiba area is base for a general description of main lithic technological changes in the Neolithic period in the Western Desert of Egypt.